2020
DOI: 10.1186/s13007-020-00629-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and comprehensive comparison of PacBio and nanopore-based RNA sequencing of the Arabidopsis transcriptome

Abstract: Background: The number of studies using third-generation sequencing utilising Pacific Biosciences (PacBio) and Oxford Nanopore Technologies (ONT) is rapidly increasing in many different research areas. Among them, plant full-length single-molecule transcriptome studies have mostly used PacBio sequencing, whereas ONT is rarely used. Therefore, in this study, we examined ONT RNA sequencing methods in plants. We performed a detailed evaluation of reads from PacBio, Nanopore direct cDNA (ONT Dc), and Nanopore PCR … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 30 publications
2
71
0
Order By: Relevance
“…Additionally, sample preparation for ONT long-read sequencing does not require PCR amplification, thus reducing possible bias, although with the consequence of reduced sequencing throughput [ 1 , 2 , 7 ]. Moreover, previous work comparing Illumina and ONT quantification of gene expression assessed the existence of a high level of correlation between the quantification of transcripts for both technologies [ 8 , 9 , 10 , 11 ], confirming that results obtained with ONT RNA-seq approaches are comparable to those obtained with short-read sequencing platforms. All of these characteristics make these two long-read sequencing technologies—ONT and PacBio—very attractive and suitable options for isoform and fusion transcript discovery and de novo transcriptomic analysis [ 12 ].…”
Section: Introductionsupporting
confidence: 69%
“…Additionally, sample preparation for ONT long-read sequencing does not require PCR amplification, thus reducing possible bias, although with the consequence of reduced sequencing throughput [ 1 , 2 , 7 ]. Moreover, previous work comparing Illumina and ONT quantification of gene expression assessed the existence of a high level of correlation between the quantification of transcripts for both technologies [ 8 , 9 , 10 , 11 ], confirming that results obtained with ONT RNA-seq approaches are comparable to those obtained with short-read sequencing platforms. All of these characteristics make these two long-read sequencing technologies—ONT and PacBio—very attractive and suitable options for isoform and fusion transcript discovery and de novo transcriptomic analysis [ 12 ].…”
Section: Introductionsupporting
confidence: 69%
“…It can read from the beginning without assembly, and obtain more transcript information, which is more conducive to comprehensive analysis. Increasing studies utilized ONT sequencers for transcriptome sequencing, such as Arabidopsis thaliana ( Cui et al, 2020 ) and Saccharomyces cerevisiae ( Jenjaroenpun et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Oxford Nanopore Technologies (ONT), a new third-generation sequencing technology, is a cost-effective and powerful method. One recent study has shown that this technology generates better quality raw data and estimates transcript levels more accurately than PacBio technology ( Cui et al, 2020 ). ONT has been broadly applied in whole genome sequencing but has rarely been used in full-length transcriptome sequencing.…”
Section: Introductionmentioning
confidence: 99%